Изменение актинового цитоскелета и кольцевых каналов питающих клеток Calliphora erythrocephala в оогенезе - Ананьина, Т.В.; Стегний, В.Н. (Фактори експериментальної еволюції організмів, 2014)
Aims. The purpose of this study was to investigate changes of the actin cytoskeleton syncytial clusters in ovaries C. erythrocephala at different stages of oogenesis. Methods. Ovarioles were stained phalloidin- FITC and DAPI. Series of optical sections were obtained using fluorescent microscope AxioImager Z.1 and module ApoTome (Zeiss). In a software module In Side 4D doing graphic reconstruction of the optical sections and analyzed by three-dimensional models of individual egg chambers, cells and nuclei. Results. We studied the changes that occur in the actin cytoskeleton cysts in different stages of oogenesis. The changes in the morphology of the ring channels which occur during normal oogenesis and violations in the formation of ring canals in the wrong formation of cysts. Conclusions. Increasing amounts of F-actin in the areas around the ring channels associated with an increase in synthetic activity of nurse cells and is aimed at ensuring the smooth movement of the cytoplasm of the nurse cells into the oocyte. Changing the shape and bandwidth ring channels may be a consequence of a breach of the formation of cysts in germarium.